People participating in the 1986 y-Walk - Unknown:::Creator::::::::::::
Negative shows Jenifer Williams, who is probably African American, and a large group of men, women, and children exercising in the YWCA's parking lot. They are all particpating in the 1986 y-Walk and the sign in tables and balloons are still set up. Some of the group are wearing tee shirts that read: "Walk for women. YWCA 1986". Jenifer Williams is in the foreground.